Students’ engagement for academic success in intensive reading - Wahyuni, Sri; Azami, Mochamad Imron (Journal of English Language Teaching and Learning (JETLE), 2024)
The aim of this research is to investigate a significant relationship between students' engagement and their success in academic focus in intensive reading at a private university in Malang, Indonesia. This research used a quantitative approach with a correlational research design to analyze the data. The sample of participants are third semester English Education Department students selected using convenience sampling technique. The data were tested and analyzed using the SPSS application and the Pearson correlation test was used. The results revealed a positive moderate category (r = 0.532, p < 0.05) between students’ engagement including behavioral, affective, social, and cognitive engagement and their academic achievement. The findings emphasize the essential role of engagement of the students in the classroom to enhance their academic success in an intensive reading context. The findings was also found that three dimensions of students' engagement correlate with academic success, including behavioral, social and cognitive engagement. Meanwhile, affective engagement is a dimension of student's engagement that has less influence on their academics. From these findings, it is hoped that educators will develop strategies to increase student engagement, especially in the context of intensive reading.